Classification of Paroxysmal Dyskinesias - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Forty six patients, ages ranging 1 to 77 years, with paroxysmal dyskinesias and classified according to precipitating factors and duration of attacks were reported from the Movement Disorder Clinic, Department of Neurology, Baylor College of Medicine, Houston, TX.